Conversion of Ammonia to Hydrazine Induced by High‐Frequency Ultrasound. Issue 48 (12th September 2021) - Humblot, Anaelle; Grimaud, Laurie; Allavena, Audrey; Amaniampong, Prince N.; De Oliveira Vigier, Karine; Chave, Tony; Streiff, Stéphane; Jérôme, François
Abstract: Hydrazine is a chemical of utmost importance in our society, either for organic synthesis or energy use. The direct conversion of NH3 to hydrazine is highly appealing, but it remains a very difficult task because the degradation of hydrazine is thermodynamically more feasible than the cleavage of the N−H bond of NH3 . As a result, any catalyst capable of activating NH3 will thus unavoidably decompose N2 H4 . Here we show that cavitation bubbles, created by ultrasonic irradiation of aqueous NH3 at a high frequency, act as microreactors to activate and convert NH3 to NH species, without assistance of any catalyst, yielding hydrazine at the bubble–liquid interface. The compartmentation of in‐situ‐produced hydrazine in the bulk solution, which is maintained close to 30 °C, advantageously prevents its thermal degradation, a recurrent problem faced by previous technologies. This work also points towards a path to scavenge . OH radicals by adjusting the NH3 concentration. Abstract : Cavitation bubbles act as microreactors to activate NH3, resulting in the formation of NH species that further recombine to hydrazine at the bubble–liquid interface. One of the advantages of this technology is the compartmentation of the as‐formed hydrazine in the bulk solution, maintained at only 30 °C, which limits its thermal degradation.